Spectrophotometric and cyclic voltammetric study of interaction of Fe(iii) with vitamin B3 and vitamin B6 (Journal of Bangladesh Academy of Sciences, 2014)
The interaction of Fe(III) with niacin and pyridoxine was investigated by UV-Vis. spectrophotometry. The metal to ligand ratio for Fe(III)- niacin system was found to be approximately 1 : 3 and for Fe(III)-pyridoxine system it was 1 : 1. The redox properties of uncoordinated Fe(III)/Fe(II) system is reversible at platinum electrode and in presence of the ligands the system was found to be quasi-reversible in nature. It was also found that in every case the system was diffusion controlled. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21339 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 143-153, 2014